Thymosin β4 Attenuates Early Diabetic Nephropathy in a Mouse Model of Type 2 Diabetes Mellitus. (March 2015) - Zhu, Jian; Su, Li-Ping; Zhou, Yue; Ye, Lei; Lee, Kok-Onn; Ma, Jian-Hua
Abstract : The chronic inflammatory processes and endothelial dysfunction play important roles in the development of diabetic nephropathy (DN); the study aims to evaluate the effect of thymosin β4 (Tβ4), which has apparent anti-inflammatory properties and is capable of improving endothelial dysfunction, in early DN in a mouse model of type 2 diabetes mellitus. KK Cg-Ay/J (KK) mice, aged 12–14 weeks, were divided into the following groups: KK control group that was treated with saline; KK Tβ4 group that was treated with Tβ4 100 ng/10 g of intraperitoneal injection once a day. Nondiabetic age-matched C57BL mice were used as additional normal control and also treated with Tβ4. The urinary albumin/creatinine ratio (ACR), plasma urea nitrogen and creatinine, body weight, fasting blood glucose and 2-hour blood glucose during oral glucose tolerance testing, blood hemoglobin A1c, cholesterol, and triglyceride were determined at baseline time and 12 weeks after Tβ4 treatment for phenotypic characterizations. The KK Tβ4 group had reduced the mean fasting blood glucose, 2-hour blood glucose during oral glucose tolerance testing, hemoglobin A1c, and triglyceride levels compared with that in the KK control group ( P < 0.05). Tβ4 treatment markedly reduced ACR (KK Tβ4 = 328.54 ± 46.14 mg/g vs. KK control = 540.34 ± 50.31 mg/g, P < 0.05). Tβ4 also significantly ameliorated renal pathological changes of KK Tβ4 mice as compared with that in KK control mice. Tβ4 treatment did not affect glucose homeostasis and urinary ACR and glomeruli of C57BL mice. These data in a novel mouse model of DN suggest that Tβ4 may ameliorate renal damage. This peptide may be a novel potential alternative agent for treatment of DN.